2019
DOI: 10.1017/s0950268819000542
|View full text |Cite
|
Sign up to set email alerts
|

Developing influenza and respiratory syncytial virus activity thresholds for syndromic surveillance in England

Abstract: Influenza and respiratory syncytial virus (RSV) are common causes of respiratory tract infections and place a burden on health services each winter. Systems to describe the timing and intensity of such activity will improve the public health response and deployment of interventions to these pressures. Here we develop early warning and activity intensity thresholds for monitoring influenza and RSV using two novel data sources: general practitioner out-of-hours consultations (GP OOH) and telehealth calls (NHS 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…In addition, RSV infection in children can place a burden on health services each winter (15). Therefore, a study has evaluated the effectiveness of various measures to decrease the positive rate of RSV (16). Our study indicated that the positive rate of RSV could be decreased with strict quarantine, face masks, and limitation of interactive and school activities.…”
Section: Discussionmentioning
confidence: 85%
“…In addition, RSV infection in children can place a burden on health services each winter (15). Therefore, a study has evaluated the effectiveness of various measures to decrease the positive rate of RSV (16). Our study indicated that the positive rate of RSV could be decreased with strict quarantine, face masks, and limitation of interactive and school activities.…”
Section: Discussionmentioning
confidence: 85%
“…The immediate and obvious challenges will be those that we will face during winter 2020/2021. Syndromic surveillance data contribute to the annual programme of influenza and other respiratory pathogens [18], with indicators that are sensitive to, and successfully monitor community-based influenza activity [9, 19, 20]. Indeed, these indicators can also be used to identify and monitor trends in other specific respiratory pathogens e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of patients with ILI is based on the standard case definition of the WHO, that is, body temperature ≥38°C with either cough or sore throat, in the absence of an alternative diagnosis ( 17 ). Besides, the ILI% was widely used in influenza surveillance to reflect the local intensity of the influenza epidemic, where ILI% = (the number of ILI cases in outpatient and emergency departments)/(the total number of outpatient and emergency cases) ×100% ( 18 , 19 ). Taking n places as an example, x 1 ( t ), x 2 ( t ), ⋯ , x n ( t ) denoted the ILI% values of the place n at the t -th week.…”
Section: Methodsmentioning
confidence: 99%